EVALUATION OF SUSTAINABLE HOUSING CONCEPT ON KAMPUNG SEPOLOH, AN INFORMAL SETTLEMENT IN SURABAYA, INDONESIA - Anita Dianingrum; Desy Rahmadaniyati (Journal of Architecture&ENVIRONMENT, 2017)
Housing is central of sustainable development since it is one of basic social conditions that determine life quality and welfare of people and place. Relationships between housing and sustainable development is addressed by sustainable housing concept, which are considered along four dimensions (environmental, social, cultural and economic).“Kampung Sepoloh” Morokrembangan is one of several informal settlements located in Surabaya Indonesia, which has been doing some efforts to improve its area through environmental approach. This is clear that The Kampung was awarded as “The Best of the Best in advanced category” on Surabaya Green and Clean Competition 2015 held by city government. Based on the achievement, it is necessary for considering the Kampung through the four dimensions of sustainable housing in order to support sustainable development.The purpose of this study is to seek any potentials related to sustainable housing implementation in “Kampung Sepoloh”. This descriptive analytic study examined the case theoretically by observation, interview, and documentation, focusing on the environmental conditions of the kampung. The result shows that “Kampung Sepoloh” has already had some achievements in each dimension. However, there are some aspects that have not run optimally, and be seen as the potentials that need to be developed.